Recent changes in the abundance of Common Pochard Aythya ferina breeding in Europe - Fox, Anthony D.; Caizergues, A.; Banik, M. V.; Devos, K.; Dvorak, M.; Ellermaa, M.; Folliot, B.; Green, A. J.; GrÃ¼neberg, C.; Guillemain, M.; HÃ¥land, A.; Hornman, M.; et al. (Wildfowl, 2016)
National accounts suggest that the Common Pochard Aythya ferina was an uncommon breeding bird throughout western Europe before 1850. Extensions to the breeding range in the late 19th century were potentially aided by the rapid development of managed fish-ponds in eastern Europe, which provided suitable novel habitat at that time. Expansion into western Europe followed in subsequent decades. Wetland and waterbody eutrophication throughout Europe, which likely provided food and cover for the birds, may have accelerated the rapid expansion from the 1950s until the early 1980s. Widespread declines in the last 30 years, especially in eastern Europe, where breeding numbers are highest, are possibly linked to intensification and/or abandonment of freshwater fish farming and changes in water quality. Studies show that Pochard gain fitness benefits from nesting in Black-headed Gull Chroicocephalus ridibundus colonies and has hence been affected by major losses of European gull colonies in the last 30 years. The spread of alien fish species such as the Carp Cyprinus carpio, which compete with Pochard for food resources, is a problem in the Mediterranean region. Changing predation pressures (in some cases linked to invasive alien mammals) are also implicated in some areas. Relatively modest numbers breeding in the UK, France and the Netherlands have remained stable or increased over the same recent span of years, confirming that different factors currently affect Pochard breeding abundance throughout its range. We urgently need better information relating to key factors affecting Pochard breeding success and abundance, which is currently showing an unfavourable conservation status throughout much of Europe.